2012
DOI: 10.1111/j.1743-7563.2012.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miR‐21, miR‐125b and miR‐191 in breast cancer tissue

Abstract: We could differentiate between breast cancer and adjacent non-tumor breast tissue as a control with a high degree of sensitivity and specificity in the Mexican population using a combined expression analysis of only two miRNA. These observations, although a proof of principle finding at this time, show that a combined expression profile of two miRNA (miR-125b/miR-191 and miR-21/miR-191) can discriminate between breast cancer and non-tumor tissue with high specificity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…For instance, miR-125b was downregulated in breast tumors compared with normal samples [6]. Moreover, overexpression of miR-125b inhibited cell growth and reduced migration and invasion in breast cancer cells [7].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, miR-125b was downregulated in breast tumors compared with normal samples [6]. Moreover, overexpression of miR-125b inhibited cell growth and reduced migration and invasion in breast cancer cells [7].…”
Section: Discussionmentioning
confidence: 98%
“…Abundant studies about the expression levels of various miRNAs and their functions in breast cancer have been reported Zhang et al, 2013). Mar-Aguilar et al (2013) demonstrated upregulation of miR-21 and miR-191 and downregulation of miR125b in breast cancer patients. Overexpression of serum miR-155 was found in breast cancer patients (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms by which miRNAs are regulated and expressed under normal or disease conditions are currently of great interest. Although miR-125b has been implicated in various cancers [12, 25-27], and might contribute to persistent inflammation [28, 29], this is the first indication about the role of miR-125b in chondrocytes inflammatory response.…”
Section: Discussionmentioning
confidence: 99%